186k views
0 votes
B -6(46 - 2) = 150A) 4-6 B) -5C) 9 D) (3)

B -6(46 - 2) = 150A) 4-6 B) -5C) 9 D) (3)-example-1

1 Answer

3 votes

To solve this equation, we need to follow the next steps:

1. Apply the distributive property:


b-6\cdot4b+6\cdot2=150\Rightarrow b-24b+12=150

2. Add the like terms, and subtract 12 to both sides of the equation:


-23b+12=150\Rightarrow-23b=150-12

3. Divide both sides of the equation by -23 (to isolate b):


(-23)/(-23)b=(150-12)/(-23)\Rightarrow b=(138)/(-23)\Rightarrow b=-6

Then, the answer to this equation is {-6} (option A).

User Herbert Sitz
by
5.4k points